SIM Puskesmas: An Integrated Management Information System for Administration, Doctor Consultations, and Web-Based Pharmacy Services at UPT Karang Anyer Using Research and Development (R&D) Approach - Nazwa Aidlia Octa Mevia; Yohana Kartika Marbun; Debi Yandra Niska; Jonatan Rio Gultom (Telkom University, 2025)
Primary health care facilities such as Community Health Centers (Puskesmas) still face challenges of inefficiency and the risk of human error due to manual data collection processes. This study aims to develop and implement a web-based Community Health Center Management Information System (SIM-PUSKESMAS) in Karang Anyer to improve service efficiency and accuracy. The study used a Research and Development (R&D) approach. The system design was carried out through Unified Modeling Language (UML) modeling, and the system implementation used web-based PHP and MySQL technologies in the XAMPP environment. The results showed the successful implementation of SIM-PUSKESMAS with role-based access rights (Admin, Doctor, Pharmacist, Patient). The main functional pages developed include Queue Management, SOAP-based Medical Records (Subjective, Objective, Assessment, Plan), Pharmacy Management, and Reports/Referrals. Comparison with conventional systems shows that this digital system significantly improves the speed of service and the accuracy of clinical data. It can be concluded that SIM-PUSKESMAS Karang Anyer is effective in ensuring data integrity, supporting better governance through instant reporting, and is a concrete step towards the digitalization of sustainable and quality health services.